P344Osteoclasts activation contributes to remodeling of the stem cell niche in diabetes. (15th July 2014) - Reni, C; Mangialardi, G; Meloni, M; Emanueli, C; Madeddu, P
Abstract: We have previously shown that mice and human patients with diabetes mellitus develop microangiopathy in bone marrow (BM) resulting in depletion of stem cells (SCs). Since the endosteal niche was the most pauperised, we decided to investigate if activation of osteoclasts (OCLs) may participate in this process through detachment of SC from the endosteal niche leading to inappropriate mobilization. The study was performed in streptozotocin-induced type 1 diabetic (T1D) mice at 5, 11 and 20 weeks from induction of diabetes and in age-matched non-diabetic controls (C). Histochemical analysis of femoral bones at late stages of DM (20 weeks) showed a profound BM remodeling characterized by reduction of the hematopoietic component, fat accumulation and bone rarefaction. The activation of osteoclastogenesis was already seen at 5 weeks as assessed by counting the number of tartrate resistant acid phosphatase (TRAP) positive OCLs in the trabecular bone (2.9±0.3 vs. 1.6±0.7 cells/mm of endosteal length in C, p<0.01). Osteoclast activation was associated with a marked increase in peripheral blood lineage- Sca1+ cKit+ (LSK) cells (0.7±0.4 vs. 0.2±0.1% of total MNCs in C, p<0.05). Unexpectedly, mRNA and protein expression of Receptor Activator of NF-κB Ligand (RANKL), an inducer of OCL differentiation and activation, was reduced in total BM at 20 and 11 weeks (mRNA: 0.3±0.01 vs. 1.2±0.3 ddCT in C; Protein: 11.8±2 vs. 28.7±5 pg/ml, p<0.05 for both comparisons) thus implying that OCL activation occurs through a non-canonical mechanism. Interestingly, we found T1D induces acidosis in BM (pH: 6.9±0.02 vs. 7.0±0.03 in C, p<0.05). Moreover, similar pH changes in culturing media increased the number of BM-derived OCL-like cells in vitro (2.0±0.3 fold increase relative to C, p<0.05) suggesting a crucial role of acidosis in OCLs activation. In summary, parallel increases in circulating SCs and endosteal OCLs occur at initial phase of T1D, before any apparent alteration of hematopoiesis. OCL activation may lead to detachment of SCs from the endosteal niche and excessive mobilization, thus resulting in BM exhaustion at later stages. OCL-induced remodeling of the endosteal niche, which contains the most primitive SCs in BM, may contribute to the impairment of regenerative capacity in T1D.